A review on surgical treatment options in gliomas - Zhongxi Yang; Chen Zhao; Shan Zong; Jianmin Piao; Yuhao Zhao; Xuan Chen (Frontiers in Oncology, 2023)
Gliomas are one of the most common primary central nervous system tumors, and surgical treatment remains the principal role in the management of any grade of gliomas. In this study, based on the introduction of gliomas, we review the novel surgical techniques and technologies in support of the extent of resection to achieve long-term disease control and summarize the findings on how to keep the balance between cytoreduction and neurological morbidity from a list of literature searched. With modern neurosurgical techniques, gliomas resection can be safely performed with low morbidity and extraordinary long-term functional outcomes.